Adenylate cyclase toxin-hemolysin relevance for pertussis vaccines. (October 2014) - Sebo, Peter; Osicka, Radim; Masin, Jiri
<x xml:space="preserve">Abstract</x> The adenylate cyclase toxin-hemolysin (ACT, AC-Hly or CyaA) is a key virulence factor of Bordetella pertussis. It targets bactericidal activities of phagocytes, such as oxidative burst and complement- or antibody-mediated opsonophagocytic killing of bacteria. Through cAMP signaling, CyaA also skews TLR-triggered maturation of dendritic cells, inhibiting proinflammatory IL-12 and TNF-α secretion and enhancing IL-10 production and Treg expansion, likely hampering induction of adaptive immune responses to Bordetella infections. Non-enzymatic CyaA toxoid is a potent protective antigen and adjuvant that boosts immunogenicity of co-administered B. pertussis antigens and improves potency of acellular pertussis (aP) vaccines in mice. This makes CyaA a prime antigen candidate for inclusion into a next generation of aP vaccines. Moreover, recombinant CyaA toxoids were recently shown to be safe in humans in frame of Phase I clinical evaluation of a CyaA-based immunotherapeutic vaccine that induces Th1-polarized CD8+ cytotoxic T-lymphocyte responses targeting cervical tumors.